2022
DOI: 10.1364/oe.476600
|View full text |Cite
|
Sign up to set email alerts
|

400Gb/s real-time coherent PON based on a silicon photonic integrated transceiver

Abstract: We experimentally demonstrate the real-time 100/200/400 Gb/s/λ coherent passive optical networks (PONs) based on silicon photonic integrated transceiver. We investigate different configuration schemes of coherent PONs including: (1) using a Erbium doped optical fiber amplifier (EDFA) as a booster at the transmitter side; (2) using a semiconductor optical amplifier (SOA) as a booster at the transmitter side; (3) using EDFA at the transmitter side and a pre-amplified SOA at receiver side; (4) using an SOA at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…[ 19,39,42–44 ] Also, they can be applied onto both curved and planar macroscale substrates. [ 18,44–47 ] For example, CSNP‐PDMS composites were applied onto concave substrates such as lenses, for use in high intensity focused ultrasound, [ 18,19,45,48 ] a therapeutic modality with wide‐ranging medical applications including tumor therapy, [ 49 ] drug delivery, [ 50,51 ] and tissue ablation. [ 52,53 ] Many studies that have focused on developing CSNP composites for OpUS generation have demonstrated promising results when these composites have been produced as free‐standing membranes.…”
Section: Introductionmentioning
confidence: 99%
“…[ 19,39,42–44 ] Also, they can be applied onto both curved and planar macroscale substrates. [ 18,44–47 ] For example, CSNP‐PDMS composites were applied onto concave substrates such as lenses, for use in high intensity focused ultrasound, [ 18,19,45,48 ] a therapeutic modality with wide‐ranging medical applications including tumor therapy, [ 49 ] drug delivery, [ 50,51 ] and tissue ablation. [ 52,53 ] Many studies that have focused on developing CSNP composites for OpUS generation have demonstrated promising results when these composites have been produced as free‐standing membranes.…”
Section: Introductionmentioning
confidence: 99%
“…This area is another example where for high datarate applications coherent has an advantage. The IM/DD solutions previously presented use either an LMS equaliser with 640 taps [10] or a Volterra equaliser of 183 length [11] . For Alamouti coding, the DSP stack is similar to the full coherent receiver [16] , however due to the short reach nature of the PON network, the chromatic dispersion compensation filter is significantly shorter, or alternatively can be integrated into the LMS equalizer.…”
Section: Performance Of Simplified Receiversmentioning
confidence: 99%
“…On the other hand, coherent technology has been proven at capacities significantly higher than 200 Gb/s even in PON applications [11] , however the cost of coherent transmitters and receivers are magnitudes higher than using IM/DD [1] . As a consequence, simplified coherent receivers have re-emerged as a research interest.…”
Section: Introductionmentioning
confidence: 99%